Branchfall dominates annual carbon flux across lowland Amazonian forests. (22nd September 2016) - Marvin, David C; Asner, Gregory P
Abstract: Tropical forests play an important role in the global carbon cycle, but knowledge of interannual variation in the total tropical carbon flux and constituent carbon pools is highly uncertain. One such pool, branchfall, is an ecologically important dynamic with links to nutrient cycling, forest productivity, and drought. Identifying and quantifying branchfall over large areas would reveal the role of branchfall in carbon and nutrient cycling. Using data from repeat airborne light detection and ranging campaigns across a wide array of lowland Amazonian forest landscapes totaling nearly 100 000 ha, we find that upper canopy gaps—driven by branchfall—are pervasive features of every landscape studied, and are seven times more frequent than full tree mortality. Moreover, branchfall comprises a major carbon source on a landscape basis, exceeding that of tree mortality by 21%. On a per hectare basis, branchfall and tree mortality result in 0.65 and 0.72 Mg C ha −1 yr −1 gross source of carbon to the atmosphere, respectively. Reducing uncertainties in annual gross rates of tropical forest carbon flux, for example by incorporating large-scale branchfall dynamics, is crucial for effective policies that foster conservation and restoration of tropical forests. Additionally, large-scale branchfall mapping offers ecologists a new dimension of disturbance monitoring and potential new insights into ecosystem structure and function.